HIGH PREVALENCE OF HUMAN PAPILLOMAVIRUS (HPV) INFECTIONS AND HIGH FREQUENCY OF MULTIPLE HPV GENOTYPES IN HUMAN IMMUNODEFICIENCY VIRUS-INFECTED WOMEN IN INDIA - Mishra, Subhash Kumar; Vishnoi, Nidhi (Journal of Biomedical and Pharmaceutical Research, 2018)
Groups of 208 human immunodeficiency virus (HIV)-infected women in India were studied for the presence of human papillomavirus with the general SPF10 PCR primer set. Virtually all (98%) women were found positive for human papillomavirus (HPV) DNA. Genotyping by the reverse hybridization line probe assay (HPV-LiPA) revealed a high prevalence of multiple genotypes (78.9% of the cases), with an average of 3.1 genotypes per patient (range, 1 to 10 genotypes). HPV 6 was the most prevalent genotype and was observed in 80 (39.2%) patients, followed by types 51 (31.9%), 11 (26.0%), 18 (24.0%), and 16 (22.5%). Of the genotypes detected, 40.9% were low-risk genotypes. Twenty-two (10.5%) patients showed normal (Pap I) cytology, 149 (71.6%) patients had inflammation (Pap II), and 28 patients (13.4%) had a Pap III score. The prevalence of high-risk genotypes increased with the cytological classification. There were no significant associations between the number of HPV genotypes detected and the cytological classification, HIV viral load, and CD4 count in these patients. In conclusion, the highly sensitive SPF10 LiPA system shows that very high proportions of HIV-infected women in Brazil is infected with HPV and often carry multiple HPV genotypes. Key-words: HIV, Human Papillomavirus, Genotypes, Women